2019
DOI: 10.1159/000497330
|View full text |Cite
|
Sign up to set email alerts
|

Observational Study to Assess Quality of Life in Patients with Pancreatic Neuroendocrine Tumors Receiving Treatment with Everolimus: The OBLIQUE Study (UK Phase IV Trial)

Abstract: Background/Aims: To assess health-related quality of life (HRQoL), treatment patterns, and clinical outcomes of adult (≥18 years) patients with advanced (unresectable or metastatic) pancreatic neuroendocrine neoplasms (PanNENs) treated with everolimus in routine clinical practice. Methods: In a prospective, non-interventional, multi-center study patients administered at least one 10 mg dose of everolimus were evaluated for change in HRQoL (EORTC QLQ-C30 Global Health Status scale) from baseline after 6 months … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 14 publications
1
30
0
Order By: Relevance
“…A significant difference in the EORTC QLQ-C30 physical functioning scale was noted by Ramage et al[ 54 ] following 6-mo treatment with everolimus, but no other significant differences were noted during this treatment period; in line with what was also shown by analysis conducted in conjunction with the RADIANT trial[ 56 ]. Likewise, sunitinib has no significant impact on global health score of EORTC QLQ-C30, but it has been shown to improve the HRQoL symptom scores of insomnia and diarrhoea compared to placebo in P-NETs[ 34 , 35 ].…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…A significant difference in the EORTC QLQ-C30 physical functioning scale was noted by Ramage et al[ 54 ] following 6-mo treatment with everolimus, but no other significant differences were noted during this treatment period; in line with what was also shown by analysis conducted in conjunction with the RADIANT trial[ 56 ]. Likewise, sunitinib has no significant impact on global health score of EORTC QLQ-C30, but it has been shown to improve the HRQoL symptom scores of insomnia and diarrhoea compared to placebo in P-NETs[ 34 , 35 ].…”
Section: Resultssupporting
confidence: 76%
“…Anxiety results were similar in the patients and in the normative population. Ramage et al[ 54 ] used the EQ-5D-5L (in addition to EORTC QLQ-C30 and GINET21), with no significant difference for the composite health index or self-rated (global) health score noted between baseline and 6-mo treatment with everolimus. The EQ-5D VAS was employed in two studies: Kulke et al[ 55 ] examined patients receiving repeated 6-weekly cycles of oral sunitinib, noting no significant difference in VAS scores over the study period, whilst Pavel et al[ 56 ] reported a reduced mean VAS from baseline to end of treatment with oral everolimus (10 mg daily, in 28-d cycles) in non-P-NET patients (63.9 ± 19.0 vs 55.3 ± 23.0, respectively) compared to P-NET patients (68.8 ± 19.9 vs 66.5 ± 20.6, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…Sunitinib and everolimus have been approved for treatment of PanNETs for many years now due to the results from the performed studies. Collected data regarding the use of both targeted agents in real world setting confirm their benefit with similar PFS and even higher RR on average in the phase IV and retrospective studies [10,[65][66][67][68][69] as you may see on Table S2. Everyday practice shows that although active, sunitinib and everolimus are derive on significant toxicity and grade 3/4 side effects for patients (Table S2).…”
Section: Evidence Supporting the Use Of Targeted Therapiesmentioning
confidence: 95%
“…However, lenvatinib has achieved a higher RR in patients with PanNETs, but the mechanism is still not clear [73]. Similarly, phase IV data from the use of sunitinib in PanNETs have also reported higher RRs than previous studies (9.3% in phase III study vs 24.5% in phase IV study) [27,68]. Whether this is reflection of better patient selection, more adequate management of toxicities, with increased exposure to active drugs, or evolution of imaging techniques can only be speculated.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…The results were negative, showing no real difference between active and placebo groups, although FACT-G is not specific to NEN (Pavel et al 2017). In view of the lack of specific HRQoL measures in trials using everolimus, the OBLIQUE (Observational Study to Assess Quality of Life in Patients with Pancreatic Neuroendocrine Tumors Receiving Treatment with Everolimus) study was performed in the United Kingdom (Ramage et al 2019), using the C30 and GINET21. The main finding was improved physical functioning at 3 months after starting therapy.…”
Section: ) Everolimusmentioning
confidence: 99%